Impact of Reversible Proton Insertion on the Electrochemistry of Electrode Materials Operating in Mild Aqueous Electrolytes: A Case Study with TiO2. Issue 3 (4th December 2022) - Makivić, Nikolina; Harris, Kenneth D.; Tarascon, Jean‐Marie; Limoges, Benoît; Balland, Véronique
Abstract: Near‐neutral aqueous electrolytes are to be preferred for the development of sustainable electrochemical energy conversion and storage devices. Protons are inherent to these electrolytes and their reactivity toward the electrode material extends beyond their own reduction, especially when reversible proton insertion takes place in the bulk electrode material from acidic or buffered electrolytes. However, a still burning question is regarding whether reversible proton insertion persists when working in unbuffered mild aqueous electrolytes, and if so, with which consequences on the functioning of the electrode material. Here this issue is addressed by examining TiO2 as a model insertion electrode in a range of mild aqueous electrolytes. Through a combination of experiments, modelling and multiphysics simulations, it is demonstrated that in a KCl‐based electrolyte, water acts as proton donor to support the reversible insertion of protons in TiO2, while in a NH4 Cl‐based aqueous electrolyte, the proton donor is NH4 + . Moreover, it is established that strong pH gradients develop at the electrode interface during proton insertion/disinsertion, highlighting their dependence on the proton donor/acceptor and rationalizing their impact on the electrode voltage. Overall, this work provides a comprehensive framework of proton‐insertion coupled electron transfer that can be easily generalized to other electrode materials. Abstract : Through a detailed experimental study of TiO2 as a model insertion material electrode over a range of buffered and unbuffered aqueous electrolytes, combined with modeling and multiphysics simulations, a comprehensive framework of the consequences of reversible proton insertion into an electrode material operating in an unbuffered aqueous electrolyte is provided here.